Through a Culturally Competent Lens: Why the Program Evaluation Standards Matter. Issue 1 (January 2016) - Gill, Sarah; Kuwahara, Robin; Wilce, Maureen
Program evaluation is an important tool for all health professionals as it enables us to learn what works, what does not, and how we can make improvements. In this article, we describe how both program staff and evaluators can use the program evaluation standards to ensure their work is culturally competent and stakeholder driven. When public health programs and their evaluations are responsive to culture and context, and they include meaningful—not token—stakeholder engagement, we produce better evaluations that are more likely to yield useful findings and lead to more effective programs. Effective programs are culturally competent programs that benefit communities in meaningful, respectful ways.